FACTORS ANALYSIS OF COMMUNITY WILLINGNESS TO FOLLOW THE COVID-19 VACCINATION PROGRAM BASED ON THEORY OF HEALTH BELIEF MODEL - Kristy, Ika Setiani; Theresia, Siwi Ikaristi Maria; Aryu, Scholastica Fina (Edu Masda Journal, 2023)
community immunity or heard Indonesia, Indonesia has promoted a COVID-19 vaccination program for the entire community. The Special Region of Yogyakarta Province is one of the provinces that implements vaccination programs intensively for the community with a high level of community willingness to participate in this vaccination program. The willingness to participate in this vaccination program is a form of a person's behavior towards the health problems faced, and this can be seen with the nursing theory, namely the Health Belief Model which assesses a person's perception to make behavioral changes following the vaccination program. The purpose of the study is to analyze the factors in the Health Belief Model nursing theory on people's willingness to participate in the COVID-19 vaccination program. The research method is quantitative with a sample of 92 respondents, the total population of Dusun Sumberan who have been vaccinated against COVID-19 doses 1 and 2. The results show that people's willingness to participate in the COVID-19 vaccination program is influenced by perceptions of the potential severity of COVID-19 disease (p = 0.73), and the benefit factor of receiving COVID-19 vaccination (p = 0.70). Meanwhile, the factors that do not affect the community's willingness are the susceptibility or ease of contracting COVID-19 (p = 0.50), the obstacle factor in participating in the vaccination program (p = 0.50), and the motivational factor in participating in the vaccination program (p = 0.50). Conclusion: The Health Belief Model is a theory that can be the base to influence people to be willing to participate in the COVID-19 vaccination program. These findings can be used to provide education to the public about the importance of participating in the vaccination program, and reduce the public doubts about COVID-19, therefore vaccine coverage increases and the herd immunity occurs in Indonesia.